Coletivo Frente 3 de Fevereiro: um estudo sobre intervenções midiáticas e políticas - Borges, Raquel Ribeiro (2021)
The present study, developed in the field of Social Sciences, seeks to analyze the artist collective Frente 3 de Fevereiro (F3F), based in São Paulo, Brazil, from the concepts of Political Art Theory. The group, like other similar agents active at their time, explored new media and technology platforms, seeking to subvert the rules and concepts of information transmission present in traditional media, in order to propagate a message that could be both politicizer and politicized, by making use of crowds as an active part of their artistic intervention and as a form of reoccupying and giving new meaning to the shared urban space. The work of referred group Frente 3 de Fevereiro through their media intervention entitled Bandeiras will be the research object of this study. The theoretical concepts of Political Art, in its understanding of critical art, will be confronted with the analysis of media interventions, in particular the intervention Bandeiras, in order to answer the following research question: Can the performance of artist collective Frente 3 de Fevereiro, in its critical and poetic sphere, be considered an example of critical art